Clinical Phenotype and Genetic Analysis of a Family with Hereditary Antithrombin Deficiency Caused by SERPINC1 Gene Mutation - Zhao, Yating; Du, Longting; Lin, Shaobin; Bai, Lu; Chen, Yao; Ye, Manman; Zhang, Shihong; Su, Chang; Zheng, Xiaohe (Thrombosis and Haemostasis, 2025)
Inherited deficiency of the antithrombin (hereditary antithrombin deficiency, AT deficiency, OMIM #613118) is a relatively rare (1:2,000–3,000) autosomal-dominant disorder with high risk of venous thromboembolism. The molecular basis of this condition has not yet fully understood, highlighting the need for further research to elucidate the underlying pathological mechanisms.This study aimed to investigate coagulation parameters and genetic phenotypes in a proband with hereditary antithrombin deficiency and her family members. Additionally, the investigation sought to provide preliminary insights for the molecular pathogenesis of this condition.Blood coagulation parameters, including plasma antithrombin activity (AT:A), antithrombin antigen (AT:Ag), protein C activity (PC:A), and protein S activity (PS:A) were measured in the peripheral blood of each family member by a Stago instrument. Peripheral blood was also extracted and sequenced to identify possible genetic mutation sites. The functional impact of variants on protein was subsequently analyzed by bioinformatics software.The proband, her mother, and brother all exhibited decreased activity and antigen of AT but normal PC and PS activity. The proband's father had normal activity and antigen levels of AT, PC, and PS. Sequencing revealed the proband's mother inherited the SERPINC1:c.661T > C,p.(Trp221Arg) heterozygous variant and her father harbored PROC:c.572_574del,p.(Lys193del) heterozygous variant while the proband as well as her brother carried both. Conservation analysis revealed that Trp221 is highly conserved across homologous species. Bioinformatics tools consistently classify the p.Trp221Arg mutation as “pathogenic” or “deleterious.” Protein modeling indicated that the p.Trp221Arg variant does not alter the protein structure but may modify glycosylation sites to affect its function.The proband and family members exhibited varying degrees of decreased levels of AT and thrombosis, which were closely associated with inheritance of SERPINC1:c.661T > C,p.(Trp221Arg).
Keywords: antithrombin; inherited AT deficiency; SERPINC1 gene; PROC gene; mutation